A comprehensive review on equal channel angular pressing of bulk metal and sheet metal process methodology and its varied applications. (November 2020) - Sadasivan, N.; Balasubramanian, M.; Rameshbapu, B.R.
Abstract: Equal Channel Angular Pressing (ECAP), being a promising technique for producing bulk ultra-fine grained material, relies on shearing the material via channels of equal cross section. The processing method keeps constantly getting modified resulting in slightly better configurations of its predecessors. A review of such processing technique modifications such as specimen orientation changes, variation in thermo-mechanical processing sequence, modifications in the die geometry etc., along with its impact on microstructural and mechanical properties are reviewed. The entire spectrum of variants of the ECAP process are classified into five major categories namely bulk metal processing, sheet metal processing, hollow section processing, powder compaction variants and extended applications. Such classification is primarily based on the product and an exhaustive review of process variants under each category are arranged in an increasing order of complexity. Conclusions are drawn on merits and demerits of existing variants of the process with suggestions for future research.